Rare vascular disorders a practical guide for the vascular specialist - Parvin, Simon D. (Tfm Pub., 2005)
The Joint Vascular Research Group has collected rare vascular conditions in a register for over a decade, and this book reviews the experience, together with the best information from the surgical literature. The authors give a practical guide on the diagnosis and management of rare vascular disorders. This book should be read by everyone who manages patients with vascular disease.